PERAN NOTARIS TERHADAP PENERAPAN ASAS KEBEBASAN BERKONTRAK PADA PERJANJIAN BAKU PEMBIAYAAN KENDARAAN BERMOTOR DENGAN JAMINAN FIDUSIA PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 18/PUU-XVII/2019 - Monica Siskaniati (Jurnal Hukum dan Kenotariatan, 2022)
Financing Agreements with Fiduciary Transfer of Ownership on Vehicles generally use a Standard Agreement or commonly known as a Standard Contract.  Fiduciary collateral must be registered at the Fiduciary Transfer of Ownership Registration Office to obtain a Fiduciary Transfer of Ownership Certificate.  Article 15 of Act Number 42 of 1999 concerning Fiduciary Transfer of Ownership states that "a Fiduciary Transfer of Ownership Certificate which includes the words "FOR JUSTICE BASED ON THE ALMIGHTY GOD".  Furthermore, Article 15 section (2) states that the Fiduciary Transfer of Ownership Certificate has the same executorial power as a court decision that has permanent legal force.  Then Article 15 states, if the debtor breaks his promise, then the Fiduciary Recipient has the right to sell the object that is the object of the Fiduciary Transfer of Ownership on his own power.The Constitutional Court Decision’s Number 18/PUU-XVII/2019 conducted a judicial review of Article 15 section (2) and (3) of the Fiducia Law with several article in The 1945 Constitution of the Republic of Indonesia. The Constitutional Court's decision caused a polemic among the public.  The results of research and normative studies conducted by the author are, a. A Financing Agreement with a Fiduciary Transfer of Ownership cannot apply the principle of freedom of contract as a whole, and there are limitations in its application because a Financing Agreement with a Fiduciary Transfer of Ownership is a Standard Agreement b. The fiduciary Transfer of Ownership deed refers to a standard financing agreement, therefore the content of the financing agreement made by the financing company must adjust to the matters regulated by laws and regulations and the Constitutional Court's Decision.  c. The execution by the creditor can still be carried out provided that the implementation is not carried out against the law and must be voluntary and both the debtor and creditor can prove that the debtor is in breach of contract.Notary as the recipient of the authority from Fiducia Law, especially in the making of the Fiduciary Transfer of Ownership Deed.  In carrying out its duties and authorities, the Notary profession also takes responsibility for the actions he has done.  Keywords: security of law, fiduciary, execution, breach of contract.